Conceptual and methodical framework for informal sector research in Nigeria (Ibadan CBN/NISER, 1995)
This report is a collaborative study between CBN and NISER on comprehensive study of the various components of Nigeria's informal sector.
Includes bibliographical references.
osa 16/01/19, 25/02/2019
Loans
Keywords: Olisadebe, E.U.; Ajakaiye, Olu; Informal sector; Informal sector - methodological; Nigeria